IMPLEMENTASI NILAI KEBANGSAAN BERSUMBER UUD 1945 DAN NKRI PADA FITUR KEAMANAN ONLINE SHOP SHOPEE YANG BERPENGARUH TERHADAP KEPUTUSAN SEKTOR KOMERSIAL NEGARA - Ade Saputra Marpaung; Edy Soesanto, Reza Dwi Fitriani (Jurnal Komunikasi, 2024)
This study aims to determine the Implementation of National Values Sourced from the 1945 Constitution and NKRI in Comparison of Shopee Online Shop Features that Affect the Decision of the State Commercial Sector. And also aims to find out the security features of a Shopee E-commerce application whether the security system is good, safe, accurate or not. because user data security is a major factor affecting the trust of application users. Users will be reluctant to use the application and choose to make purchases elsewhere if they feel their personal data is not safe. Internet users' fears have grown as a result of increased cyberattacks and data leaks in recent years. Therefore, better and more secure security management is needed for user data management. Additionally, the data from this study will be used to inform future investigations that will be conducted to establish relationships between different variables. The following is how the results of the literature study are presented in this article: 1. Shopee for e-commerce, 2. perceived security, 3. security, and 4. security management